2022
DOI: 10.1182/blood.2022016040
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell multiomics reveal the scale of multilayered adaptations enabling CLL relapse during venetoclax therapy

Abstract: Venetoclax inhibits the pro-survival protein BCL2 to induce apoptosis and is a standard therapy for chronic lymphocytic leukemia (CLL), delivering high complete remission rates and prolonged progression-free survival in relapsed CLL, but with eventual loss of efficacy. A spectrum of sub-clonal genetic changes associated with venetoclax resistance have now been described. To fully understand clinical resistance to venetoclax, we combined single-cell short- and long‑read RNA‑sequencing to reveal the previously u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 43 publications
2
50
0
Order By: Relevance
“…The second major mechanism driving resistance we identified in our S63845-resistant cells was upregulation of the pro-survival proteins BCL-XL and A1. Many studies have reported the overexpression of pro-survival BCL-2 proteins as resistance factors for venetoclax therapy, including in patient samples and in in vitro whole genome CRISPR/Cas9 screens [35,37,39,52,53]. In our study, Eµ-Myc lymphoma cells that had achieved resistance to S63845 through upregulation of BCL-XL and A1 also showed resistance to etoposide treatment due to the over-expression of these pro-survival proteins preventing apoptosis.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The second major mechanism driving resistance we identified in our S63845-resistant cells was upregulation of the pro-survival proteins BCL-XL and A1. Many studies have reported the overexpression of pro-survival BCL-2 proteins as resistance factors for venetoclax therapy, including in patient samples and in in vitro whole genome CRISPR/Cas9 screens [35,37,39,52,53]. In our study, Eµ-Myc lymphoma cells that had achieved resistance to S63845 through upregulation of BCL-XL and A1 also showed resistance to etoposide treatment due to the over-expression of these pro-survival proteins preventing apoptosis.…”
Section: Discussionmentioning
confidence: 50%
“…Resistance to BH3-mimetic drugs is a critical and emerging issue which threatens to limit the benefit of this class of anti-cancer therapy. While genetic changes underlying resistance to the BCL-2 inhibitor venetoclax are beginning to be uncovered [5,23,26,[35][36][37][38][39], less attention has been focused on resistance to MCL-1 inhibitors, which have entered clinical trials for diverse haematological malignancies [5]. To this end, we sought to identify factors that could confer resistance to MCL-1 inhibitors using murine and human models of highly aggressive, MYC-driven lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, heterogeneous molecular mechanisms of resistance have been observed in vitro as well as under clinical circumstances. The spectrum of molecular changes reported to be associated with acquired resistance includes alterations in the pro-survival gene BCL2 diminishing venetoclax binding, overexpression of the anti-apoptotic BCL-XL, Bcl-2, MCL1, and XIAP, and the emergence of complex karyotypes [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Mitochondrial metabolic reprogramming has also been reported as a putative driver mechanism of venetoclax resistance through AMPK-regulated oxidative phosphorylation in patients with refractory CLL [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, several additional BCL2 mutations, e.g., D103Y directly disrupting the BH3 binding P4 pocket, have been observed in CLL patients, unveiling various cooperating mutational patterns with coexisting mutations and overexpression of the pro-survival proteins BCL-XL and MCL1 [ 13 , 14 , 20 , 21 ]. Although the proportion of CLL cells carrying resistance-associated molecular changes may vary widely from minor subclones to large CLL compartments, subclonal presence and cumulative abundance of genetically and/or transcriptionally altered leukemic cells are reported in the majority of cases [ 12 , 13 , 20 ]. Intriguingly, subclonality of mutation-bearing or BCL-XL/MCL1-overexpressing CLL cells has been observed even in samples obtained at the time of relapse or disease progression, implying a significant role of the permissive microenvironment and cooperating genetic and epigenetic events in driving acquired venetoclax resistance leading to overt clinical relapse [ 12 , 13 , 14 , 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the upregulation of these anti-apoptotic proteins contributes directly to venetoclax resistance, and the downregulation of MCL-1 or BCL-X L restores venetoclax sensitivity [29]. The upregulation of MCL-1 is common in leukemic cells following venetoclax exposure, and elevations in MCL-1 subside with venetoclax discontinuation [30]. The reduction in MCL-1 following venetoclax cessation forms the basis of a strategic molecular rationale to reduce venetoclax resistance: stopping or shortening the duration of venetoclax after a maximal response is reached.…”
Section: Modulation Of Apoptosis: Bcl-2 Inhibitionmentioning
confidence: 99%